2018
DOI: 10.1038/s41418-017-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

eIF2α phosphorylation is pathognomonic for immunogenic cell death

Abstract: The phosphorylation of eIF2α is essential for the endoplasmic reticulum (ER) stress response, the formation of stress granules, as well as macroautophagy. Several successful anticancer chemotherapeutics have the property to induce immunogenic cell death (ICD), thereby causing anticancer immune responses. ICD is accompanied by the translocation of calreticulin (CALR) from the ER lumen to the plasma membrane, which facilitates the transfer of tumor-associated antigens to dendritic cells. Here we systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(155 citation statements)
references
References 54 publications
10
145
0
Order By: Relevance
“…Despite the phosphorylation of eIF2α, neither the activation of ATF4 nor that of DDIT3 was observed. Similar findings were recently reported for different ICD drugs reinforcing the notion of the phosphorylation of eIF2α as an important ICD hallmark (Bezu et al , ). In line with this observation, other ICD hallmarks (such as the exposure of CALR, the secretion of ATP, and the exodus of HMGB1) were detected in response to redaporfin‐PDT and, more importantly, cells killed in vitro by redaporfin‐PDT were able to vaccinate mice against rechallenge with live cancer cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the phosphorylation of eIF2α, neither the activation of ATF4 nor that of DDIT3 was observed. Similar findings were recently reported for different ICD drugs reinforcing the notion of the phosphorylation of eIF2α as an important ICD hallmark (Bezu et al , ). In line with this observation, other ICD hallmarks (such as the exposure of CALR, the secretion of ATP, and the exodus of HMGB1) were detected in response to redaporfin‐PDT and, more importantly, cells killed in vitro by redaporfin‐PDT were able to vaccinate mice against rechallenge with live cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…eIF2α phosphorylation without the activation of ATF4 and DDIT3 was recently described as a hallmark of ICD (Bezu et al , ). Indeed, redaporfin‐based PDT induced other hallmarks of ICD such as plasma membrane calreticulin exposure, as well as the release of ATP and HMGB1 from cancer cells in vitro (Appendix Fig S4).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, TERS-primed cancer cells grow more quickly in vivo than their control counterparts 62 . Some cell-deathpromoting chemotherapeutic agents such as anthracyclines and oxaliplatin also trigger a partial ER stress response in cancer cells, which manifests with PERKdependent eIF2α phosphorylation but not with ATF4, ATF6 and XBP1s activation 63 . Phosphorylated eIF2α favours the translocation of ER chaperones including calreticulin (CALR) and protein disulfide-isomerase A3 (PDIA3) from the ER lumen to the cell surface 64 , where they act as 'eat-me' signals to promote phagocytosis of dying cancer cells by dendritic cells and hence initiate anticancer immunity 17 .…”
Section: Box 1 | the Dna Damage Response At A Glancementioning
confidence: 99%
“…However, in response to certain stimuli, including anthracyclines, oxaliplatin and hypofractionated irradiation, apoptosis can mediate robust immunostimulatory effects 17,173 . Such a form of immunogenic cell death (ICD) mechanistically relies on the activation of intracellular stress responses, including (but perhaps not limited to) a partial ER stress response (culminating in the exposure of pro-phagocytic signals; see above) 63 , autophagy (resulting in ATP release; see above) 110 and intracellular nucleic acid sensing (resulting in type I IFN release, see above) 25,174 . Interestingly, apoptotic ICD depends on CASP8 (REF.…”
Section: Rigi-like Receptorsmentioning
confidence: 99%
“…Furthermore, cytofluorometric analysis showed that T0901317 induced significant translocation of CRT to the cell surface in HCT116 cells ( Figure 1B). As CRT exposure occurs as a consequence of ER stress-induced phosphorylation of eIF2α, 17,18 we then examined expression levels of eIF2α and P-eIF2α after treatment with T0901317. As shown in Figure 1C, HCT116 cells treated with T0901317 increased expression of P-eIF2α.…”
Section: Lxr Agonists Induce Crt Expression In Colon Cancer Cellsmentioning
confidence: 99%